2020
DOI: 10.1016/j.vaccine.2020.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal conjugate vaccine primes mucosal immune responses to pneumococcal polysaccharide vaccine booster in Papua New Guinean children

Abstract: Introduction Invasive pneumococcal disease remains a major cause of hospitalization and death in Papua New Guinean (PNG) children. We assessed mucosal IgA and IgG responses in PNG infants vaccinated with pneumococcal conjugate vaccine (PCV) followed by a pneumococcal polysaccharide vaccine (PPV) booster. Methods Infants received 7-valent PCV (7vPCV) in a 0–1–2 (neonatal) or 1–2-3-month (infant) schedule, or no 7vPCV (control). At age 9 months all children received 23-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The most common serotypes recorded from the listed countries were serotype 6A cases recorded from New Guinea (2023) [31], Thailand (2023)[80],Nigeria (2023)[81],Bangladesh & India (2021) [46], Ecuador (2021) [70], and the Dominican Republic (2021) [70]; serotype 19A cases reported from the Nigeria (2023) [31,81], Thailand (2023) [80],New Guinea (2023) [31],Dominican Republic (2021), Bangladesh (2021) [46], India (2021) [46], Ecuador (2021) [70], and Malawi (2022); serotype 1 cases reported from Kenya (2012 [89, 90], 2017 (52,83)) and Nigeria (2018); serotype 5 cases reported from Nigeria (2018) [75], Vietnam (2021), Germany (2021)[67], and Kenya (2012[89, 90], 2017 [29]); and serotype 7F cases reported from Vietnam (2021) [77], Germany (2021)[67], and Kenya (2012 [89, 90], 2017) [89,90]. There is a considerable increase in PCV13 serotype numbers in 2020 and 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common serotypes recorded from the listed countries were serotype 6A cases recorded from New Guinea (2023) [31], Thailand (2023)[80],Nigeria (2023)[81],Bangladesh & India (2021) [46], Ecuador (2021) [70], and the Dominican Republic (2021) [70]; serotype 19A cases reported from the Nigeria (2023) [31,81], Thailand (2023) [80],New Guinea (2023) [31],Dominican Republic (2021), Bangladesh (2021) [46], India (2021) [46], Ecuador (2021) [70], and Malawi (2022); serotype 1 cases reported from Kenya (2012 [89, 90], 2017 (52,83)) and Nigeria (2018); serotype 5 cases reported from Nigeria (2018) [75], Vietnam (2021), Germany (2021)[67], and Kenya (2012[89, 90], 2017 [29]); and serotype 7F cases reported from Vietnam (2021) [77], Germany (2021)[67], and Kenya (2012 [89, 90], 2017) [89,90]. There is a considerable increase in PCV13 serotype numbers in 2020 and 2021.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important methods for avoiding pneumococcal illness is vaccination with PCVs. In certain studies, persons without a vaccine [38,40,46,83,85,[91][92][93][94] or with partial immunizations [31,36,42,45,47,[52][53][54][55][56][57][58][59][60][61][62]79, 81] had a higher frequency of the disease than those who were vaccinated. This highlights the importance of vaccination initiatives in reducing the incidence of pneumococcal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, anti‐PnPS IgA and IgM were only measured in blood, not in mucosal tissues or secretions. While the PCV and PnPS vaccine, after priming with PCV, have been shown to be able to induce protective mucosal IgA antibodies [ 27 , 28 ], it is unknown whether this also occurs after immunization with PnPS vaccine alone. Most infectious pathogens enter the host via mucosal surfaces, where mucosal IgA represents the hallmark of immune responses [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to salivary IgA antibody, we observed a difference between the groups, with a higher post-vaccination increase in salivary IgA in Vivomixx ® supplemented patients, in accord with the study of Lue et al showing that, of all classes of anti-CPS antibody in saliva and tears, PPV levels increase the most. The authors reported a 2.0-fold increase of salivary IgA levels detected in the saliva of PCV-immunized children [32,33] as result of an immunostimulatory effect of probiotic bacteria [34,35].…”
Section: Discussionmentioning
confidence: 99%